Protecting Digital Dignitas: Highlighting Legal Protection and Responsibility in Personal Data Security Crime in Indonesia's Online Marketplace World - Dinda Yunisa Yunisa; Adelina Mariani Sihombing; Chelsea Mutiara Putri; Nurul Hasanah (Universitas Sumatera Utara, 2023)
Today the development of technology is increasingly massive and gave birth to a form of intelligence called Artificial Intelligence/AI. Economic potential and threats of personal data leakage awaiting immediate investigation. The concept of digital dignity is closely related to personal data security because in the digital era, leakage of personal data can harm users and violate their privacy rights. This paper aims to provide a juridical analysis of digital identity protection by highlighting legal protection and marketplace responsibility for cases of personal data leakage in Indonesia. The type of research used is normative legal research using statutory regulations, case studies and concept approaches. This research uses secondary data as the main data and uses literature study as a material collection technique. All materials that have been collected are then inventoried, classified, and analyzed using descriptive analysis which aims to describe the problem so that innovative solutions are obtained. There are several deficiencies in the marketplace security system and regulations governing the protection of personal data. This can be handled with marketplace supervisory agencies or supervisory parties, implementing standardized security and regulations on marketplaces specifically as well as internal and external digital identity protection regarding the several parties involved in it.